Risk Factors of Computer Vision Syndrome in Lecturers and Academic Staff: A Literature Review - Fauziah, Aswin; Solikhah, Solikhah; Hariyono, Widodo (Disease Prevention and Public Health Journal, 2025)
Background: Computer Vision Syndrome (CVS) is becoming an important issue among lecturers and academic staff due to the increasing use of digital devices. CVS causes symptoms such as dry eye fatigue, headaches, and neck and back pain that can affect teaching quality and individual well-being. This study aims to understand the relationship of CVS variables in lecturers and academic staff and management with existing literature; Method: A literature review was conducted by searching electronic data-based articles including Google Scholar and Pubmed using the keywords Computer Vision Syndrome, lecturer, academic staff, management. Inclusion criteria included articles from national and international accredited publications 2019-2024, full text, open access and cross sectional study research design. 10 articles were selected for analysis according to Prisma Guidelines; Results: Analysis of the literature showed that CVS risk factors consisted of individual factors, namely male, computer use more than four hours a day; for environmental factors, ergonomics and lighting were also influential. The importance of eye health awareness, educational interventions, adjustments to work ergonomics and the practice of eye exercises can reduce the risk of CVS and Conclusion: CVS is a significant problem among computer users especially in academic settings. Individual and environmental factors influence CVS symptoms. Prevention and management require a comprehensive approach with ergonomic adjustments, regular breaks and educational interventions. Eye exercise programs are effective in reducing symptoms. The challenge lies in developing evidence-based strategies to address individual responses. It is hoped that these measures can reduce the prevalence of CVS, improving the health and well-being of computer users.